Local Economic Development: An Alternative Development Approach for Zambia - Thakur, Sangeeta (Journal of Global Economy, Business and Finance, 2024)
Since attaining independence in 1964, Zambia produced several national development plans. However, the development plans had little impact on development imperatives in as far as reducing poverty and inequality levels were concerned. This study therefore, reviews Zambia’s past national development policy plans i.e., from 1964 to 2021 and seeks to propose a change of approach to adopt the local economic development process which is more effective in combating high levels poverty and inequalities. The study used a qualitative desk-top study that employed the historical-critical discourse analysis approach to investigate the effectiveness of the past national development plans. The study revealed that the development approach that Zambia adopted did not significantly impact on the reduction of inequality and poverty levels. The study recommends that Zambia should consider embarking on an effective LED approach as an alternative development approach that would deliver the country’s development imperatives.